Memorandum of Understanding between BRAC University and South Asian Institute of Advanced Legal and Human Rights Studies (2007) - BRAC University; South Asian Institute of Advance legal and Human Rights Studies (BRAC University and South Asian Institute of Advanced Legal and Human Rights Studies, 2013)
This Memorandum of Understanding dated (MoU) dated 11 December 2007 between BRAC University (here in after referred to as “BU”) having its administrative establishment at 66 Mohakhali, Dhaka-1212 and the South Asian Institute of Advanced Legal and human Rights studies (hereinafter referred to as ''SAILS") a society registered under the Societies Registration Act. 1860 No. S-6887 (75)/07) for the time being having its registered office at 122-124 Motijheel C/A. Dhaka-1000 sets firth the understanding and agreements reached between the parties relating to the design, delivery and conferral of ' postgraduate degrees, Diplomas and certificates as sell as cooperation between the parties on academic (including teaching and research) and related administrative matters.